2024
DOI: 10.1039/d3tc03968d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanofluorochromism and self-recovery of alkylsilylpyrene-1-carboxamides

Yuichi Hirai,
Anna Wrona-Piotrowicz,
Janusz Zakrzewski
et al.

Abstract: The stimuli-responsive properties of mechanofluorochromic pyrene derivatives, including spontaneous solid-state recovery processes, are elucidated through crystallography, spectroscopy, and nanomechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…(b) MRL and mechanical properties of boron complexes (reproduced with permission from ref , copyright 2013 John Wiley & Sons, Inc., and ref , copyright 2015 IUCr Journals). (c) MRL response, intermolecular interactions, mechanical parameters, and crystal void volumes of pyrene derivatives (reproduced with permission from ref , copyright 2024 The Royal Society of Chemistry).…”
Section: Sense Deform and Healsupporting
confidence: 56%
See 3 more Smart Citations
“…(b) MRL and mechanical properties of boron complexes (reproduced with permission from ref , copyright 2013 John Wiley & Sons, Inc., and ref , copyright 2015 IUCr Journals). (c) MRL response, intermolecular interactions, mechanical parameters, and crystal void volumes of pyrene derivatives (reproduced with permission from ref , copyright 2024 The Royal Society of Chemistry).…”
Section: Sense Deform and Healsupporting
confidence: 56%
“…The chromic direction upon grinding was influenced by packing motifs (Section 3.1), while spontaneous molecular rearrangement was delineated by the nanomechanical constants, rendering the distribution pattern and magnitude of intermolecular interactions and the volume of the crystal voids. 139 Thus, mechanical parameters are essential for understanding the stiffness, deformability, and reversibility of deformation of a material, among other factors. However, since Ramamurty et al provided an overview of NI techniques for molecular crystals in 2013, describing MRL and ML as "stressinduced phenomena that are largely unexplored", 198 only a few studies have reported a comprehensive set of data to date.…”
Section: Quantity Of Deformationmentioning
confidence: 99%
See 2 more Smart Citations